Assessment of operating temperature within the new pavilion for slag management in Terni. Issue 1 (1st April 2022) - Manni, Mattia; Fabiani, Claudia; Nicolini, Andrea; Pisello, Anna Laura; Rossi, Federico; Cotana, Franco
Abstract: The whole metallurgic sector produces up to 200 million tons of slag, which are tapped from the blast furnace (at a temperature of 1, 500°C), and then need to be cooled down before disposal. These cooling processes are generally conducted open-air, significantly affecting local environmental quality of the surroundings. The present study aims at investigating the potential of an innovative slag cooling system housed within a pavilion, designed in order to minimize the emission of dust and pollutants out from the metallurgic plant. Such a system consists of a depressurized environment whose top surface is treated with black pigments and cooled down by water streams above it. Air is continuously extracted and then adequately filtered before being released outdoor. A numerical model was elaborated for evaluating the main heat flows developed within and through the pavilion's envelope for the case study in Terni, central Italy. Once the physical and geometrical properties of the slag and the pavilion were defined, the heat exchanged with the air and water due to convection, as well as the latent heat dissipated through water evaporation was quantified. Results demonstrated the effectiveness of the water-based cooling system in keeping the roof temperature lower than 328 K without compromising the mechanical properties of the material. The evaporated water mass ranged between 4.2 kg h −1 and79.6 kg h −1 and was strongly influenced by seasonal weather conditions.